Pengaruh Model Pembelajaran Talking Stick Terhadap Hasil Belajar Matematika Pecahan Siswa Kelas V SD Negeri 102048 Tanjung Beringin - Nadia Nadia; Umar Darwis (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2023)
This study aims to examine the effect of the Talking Stick learning model on student learning outcomes in fraction math in class V at SD Negeri 102048 Tanjung Beringin. The research method used was an experiment with an experimental group and a control group. Pretest and posttest data were taken from both groups and analyzed using relevant statistical tests. The results showed a significant difference between the pretest and posttest in both groups. The average pretest score of the experimental group was 44, while the average pretest score of the control group was 40. After treatment using the Talking Stick learning model, the average posttest score of the experimental group increased to 80, while the average posttest score of the control group was 75. Statistical analysis showed that the data of student learning outcomes in both groups, both pretest and posttest, were normally distributed. In addition, the homogeneity of variance test showed that there was no significant difference in variability between the two groups, indicating homogeneity of data variance. The paired t-test showed a significant difference between the pretest and posttest in both groups, indicating that the Talking Stick learning model has a significant effect on student learning outcomes in both groups. Therefore, it can be concluded that the Talking Stick learning model has a significant effect on student learning outcomes in fraction math in class V at SD Negeri 102048 Tanjung Beringin. This research provides important implications in the development of effective mathematics learning approaches and can be used as a guideline in improving learning methods in schools